CAMBRIDGE CURRICULUM IMPLEMENTATION AT SMP MADINA ISLAMIC SCHOOL - Zahra Nabilla Islam; Nurul Hasanah Fajaria (Akademika : Jurnal Teknologi Pendidikan, 2022)
This study aims to describe and analyze the implementation of the international curriculum, namely the Cambridge curriculum, to determine the concept of the Cambridge curriculum and the manifestation of the concept, namely the application of the Cambridge curriculum and to determine the results achieved in implementing the Cambridge curriculum at Madina Islamic School. This research is qualitative descriptive research. Data collection was done by interview, observation, and documentation methods. To check the validity of the data obtained, the researcher used the source triangulation method. The results of the research conducted indicate that (1) The form of application of the Cambridge curriculum at Madina Islamic School is by requiring all students to have a Cambridge certificate in at least one field of study by taking the Cambridge certification exam. Coaching is held once a week for one subject or one subject as well as intensive coaching is carried out for two days before the Cambridge certification exam. (2) The inhibiting and supporting factors of the implementation of the Cambridge curriculum in student learning from the results show that the guidance and assistance carried out by the school, namely the principal and the teacher council to their students through the implementation of the Cambridge curriculum in student learning so that students increasingly show their true identity character.